An Analysis of Requesting Strategies in Aladdin (2019) Movie - Eka Putri Lestari; Usep Muttaqin; Tri Wahyu Setiawan Prasetyoningsih (Paradigma Lingua, 2024)
This study aims to analyze the strategies of making requests uttered by the characters in Aladdin (2019) using Trosborg’s (1995) theory. The method used in this study is descriptive-qualitative research. The data is taken from the utterances in the dialogue uttered by the characters that contain strategies for making requests. The result shows that all of the strategies of requests were found in this study. They are hints, questioning the hearer’s ability and willingness, suggestory formulae, statements of the speaker’s wishes and desires, statements of the speaker’s needs and demands, statements of obligation, performative, and imperative. The most dominant strategy that is widely used is the imperative. This strategy appears 19 times (39.58%) from a total of 48 data requests. To sum up, the imperative strategy helps the characters to convey the request in an obvious and direct way. Thus, it is more effective, efficient, and concise to be used by the characters who have higher positions and power. Keywords: Aladdin (2019), Context, Pragmatics, Request Strategies, Trosborg